Putting GM technologies to work: Public research pipelines in selected African countries - Sithole-Niang, Idah; Cohen, Joel I.; Zambrano, Patricia (2004)
Can public policies and research institutions in African countries provide safe and useful genetically modified (GM) food crops? This is an urgent question, recognizing that advancing GM food crops can be difficult, affected by global debate, and various regulatory protocols. Reaching farmers has been achieved in several countries only for GM cotton for insect resistant while approvals for food and feed crops lag behind. To address this question, we identified and examined public research pipelines for GM crops in Egypt, Kenya, South Africa and Zimbabwe. Genetic transformation events are reported for 21 crops. Findings are presented for events nearing final stages of development, analysis of the crops, traits and genes involved, and details regarding biosafety. The paper concludes with a summary offering various policies, institutional and regulatory suggestions.